Impaired social contacts with familiar anesthetized conspecific in CA3‐restricted brain‐derived neurotrophic factor knockout mice. (4th September 2018) - Ito, Wataru; Huang, Howard; Brayman, Vanessa; Morozov, Alexei
Abstract : Familiarity is conveyed by social cues and determines behaviors toward conspecifics. Here, we characterize a novel assay for social behaviors in mice—contacts with anesthetized conspecific—which eliminates reciprocal interactions, including intermale aggression and shows behaviors that are independent of the demonstrator's activity. During the initial 10 minutes (phase‐1), the wild‐type (WT) subjects contacted the anesthetized conspecifics vigorously regardless of familiarity. During the subsequent 80 minutes (phase‐2), however, they contacted more with familiar than unfamiliar conspecifics. We then applied this test to highly aggressive mice with a hippocampal CA3‐restricted knockout (KO) of brain‐derived neurotrophic factor (BDNF), in which aggression may mask other social behaviors. The KO mice showed less preference for contacting familiar conspecifics than did WT mice during phase‐2 but no differences during phase‐1. Among nonsocial behaviors, WT mice also spent less time eating in the presence of familiar than with unfamiliar conspecifics, which was not seen in KO mice. In addition, KO mice exhibited reduced pain sensitization. Altogether, these findings suggest that CA3‐specific deletion of BDNF results in deficits in circuits that process social cues from familiar conspecifics as well as pain and may underlie empathy‐like behaviors. Abstract : A decreased preference to interact with familiar anesthetized conspecific in male BDNF conditional KO mice.